2020
DOI: 10.1038/s41598-020-64936-y
|View full text |Cite
|
Sign up to set email alerts
|

Core versus cuttings samples for geochemical and petrophysical analysis of unconventional reservoir rocks

Abstract: core samples from petroleum wells are costly to obtain, hence drill cuttings are commonly used as an alternative source of rock measurements for reservoir, basin modelling, and sedimentology studies. However, serious issues such as contamination from drilling mud, geological representativeness, and physical alteration can cast uncertainty on the results of studies based on cuttings samples. this paper provides a unique comparative study of core and cuttings samples obtained from both vertical and horizontal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…1 ). This is similar to Rock–Eval results on petroleum source rock samples that contain heavy hydrocarbons and bitumen due to lower maturity or are contaminated by drilling additives (Abrams et al, 2017 ; Jiang et al, 2019 ; Sanei et al, 2020 ).
Fig.
…”
Section: Resultssupporting
confidence: 86%
“…1 ). This is similar to Rock–Eval results on petroleum source rock samples that contain heavy hydrocarbons and bitumen due to lower maturity or are contaminated by drilling additives (Abrams et al, 2017 ; Jiang et al, 2019 ; Sanei et al, 2020 ).
Fig.
…”
Section: Resultssupporting
confidence: 86%
“…The δ 34 S evap correlation presented in this study is surprising in that the 42/28-2 sediments have been exposed and saturated with drilling fluids: unfortunately, there is no record of what drilling fluids were used when coring. Samples can be fully covered in fluids during the drilling process and washing them away entirely is difficult (Kubo et al, 2016), thus potentially impacting the integrity of sample geochemistry (e.g., Stuckman et al, 2019;Sanei et al, 2020). δ 34 S evap values in drill cuttings are vulnerable to contamination by drilling fluids, which can be characterised by a range of different chemical compositions (Ball et al, 2012).…”
Section: Preservation Of Primary δ 34 S Evap Signalsmentioning
confidence: 99%
“…However, recent studies have demonstrated the validity of drill cuttings for carbon isotope stratigraphy, in part through comparison with δ 13 C records from cored intervals and outcrop (Metzger et al, 2014;Eldrett et al, 2021). Sanei et al (2020) demonstrated that with sufficient cleaning of drill cuttings, total organic carbon (TOC) values are comparable to those directly obtained from cored intervals. To our knowledge, only a single study has demonstrated the suitability of borehole cuttings for sulphur isotope stratigraphy (Cao et al, 2016), however, the authors did not demonstrate the validity of drill cuttings for evaporitic lithologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, mudstone successions are rarely cored during wellsite operations and source rock studies are thus commonly based on drill cuttings (Mansour et al, 2020; Rosenberg et al, 2021; Silva et al, 2017). While drilling mud contamination may pose a serious issue for organic geochemical characterisation of cuttings (Sanei et al, 2020), its influence on the elemental assemblage is generally negligible (Craigie, 2018). Elemental studies of drill cuttings have been shown to be highly useful in mapping chemostratigraphic zones (Craigie, 2015; Wright et al, 2010) and for multilateral well steering of shale plays (Hildred, 2012; Hildred et al, 2011; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%